1997
DOI: 10.1107/s0108768196014048
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Engineering Using Bisphenols and Trisphenols. Complexes with Hexamethylenetetramine (HMTA): Strings, Multiple Helices and Chains-of-Rings in the Crystal Structures of the Adducts of HTMA with 4,4'-Thiodiphenol (1/1), 4,4'-Sulfonyldiphenol (1/1), 4,4'-Isopropylidenediphenol (1/1), 1,1,1-Tris(4-hydroxyphenyl)ethane (1/2) and 1,3,5-Trihydroxybenzene (2/3)

Abstract: The 4,4'-bisphenols (1), X(C6H4OH)2 [a, X = nil; b, X = O; c, X = S; d, X = 502; e, X = CO; f, X = CH2; g, X = CMe2; h, X = C(CF3)2], when co-crystallized from alcoholic solutions with hexam-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The most likely intermolecular interaction has been attributed to the possibility of hydrogen bonding that can form between the four equivalent nitrogens of HMTA and electron accepting functional groups. For example, previous diffraction studies have shown the possibility that one HMTA can cocrystallize with phenols . The corresponding 14 N quadrupole resonance spectroscopy has generally been used to characterize the intermolecular interactions, including hydrogen bonds …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely intermolecular interaction has been attributed to the possibility of hydrogen bonding that can form between the four equivalent nitrogens of HMTA and electron accepting functional groups. For example, previous diffraction studies have shown the possibility that one HMTA can cocrystallize with phenols . The corresponding 14 N quadrupole resonance spectroscopy has generally been used to characterize the intermolecular interactions, including hydrogen bonds …”
Section: Resultsmentioning
confidence: 99%
“…For example, previous diffraction studies have shown the possibility that one HMTA can cocrystallize with phenols. 20,35 The corresponding 14 N quadrupole resonance spectroscopy has generally been used to characterize the intermolecular interactions, including hydrogen bonds. 20 Since we are dealing with various solutions and the need to follow the crosslinking reaction, instead of using NMR, we used infrared spectroscopy to characterize intermolecular interactions in the prepolymer and furfural.…”
Section: Analysis Of the Molecular Interaction Between Hmta And The Pmentioning
confidence: 99%
“…Aoyoma et al have reported 11-fold catenation in a tetraphenol−benzoquinone adduct. Alternatively, the packing in the diamondoid network can be visualized by considering the subunits of the adamantanoid cage as intertwining of eight 2 1 helical structures . The pitch of the helix is 25 Å (Figure a).…”
Section: Resultsmentioning
confidence: 99%
“…6 Changes in packing motifs resulting from small variations in molecular structure or substituents have also been observed with other compounds capable of homomeric hydrogen bonding (for example, carboxylic acids, 7 oximes 8 and secondary enaminones 9 ), as well as in many heteromeric hydrogen-bonded structures (for example, bisphenol-amine co-crystals). 10 Our interest in the title compounds originated from synthetic investigations first performed in the 1980s, when we prepared several 1-(2-halophenyl)cyclohexanecarboxamides as part of a model study to identify suitable precursors for the construction of oxindoles bearing spirocyclic rings at C-3. 11,12 These spiro-oxindoles in turn served as models for developing methodology aimed at the total synthesis of the complex spirooxindole alkaloid gelsemine.…”
Section: Introductionmentioning
confidence: 99%